2016
DOI: 10.1002/ecy.1460
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of functional diversity loss on ecosystem functions are influenced by compensation

Abstract: Abstract.Understanding the impacts of biodiversity loss on ecosystem functioning and services has been a central issue in ecology. Experiments in synthetic communities suggest that biodiversity loss may erode a set of ecosystem functions, but studies in natural communities indicate that the effects of biodiversity loss are usually weak and that multiple functions can be sustained by relatively few species. Yet, the mechanisms by which natural ecosystems are able to maintain multiple functions in the face of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…Moreover, our study indicated that the effects of grazing intensities on perennial grasses (both bunch and rhizome grasses) were not linear in the nondrought year. This might have occurred because perennial grasses—as dominant PFGs in the typical steppe on the Mongolian Plateau (Li et al., ; Ma et al., ; Pan et al., )—are resistant to grazing because of their acquisitive‐conservative competition for resources (Bai et al., ; Zheng et al., ). This is also likely because the dominant PFGs were more highly sensitive to changes in environmental variation than to grazing intensities (Milchunas et al., 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our study indicated that the effects of grazing intensities on perennial grasses (both bunch and rhizome grasses) were not linear in the nondrought year. This might have occurred because perennial grasses—as dominant PFGs in the typical steppe on the Mongolian Plateau (Li et al., ; Ma et al., ; Pan et al., )—are resistant to grazing because of their acquisitive‐conservative competition for resources (Bai et al., ; Zheng et al., ). This is also likely because the dominant PFGs were more highly sensitive to changes in environmental variation than to grazing intensities (Milchunas et al., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Because species richness was tallied as the total number of species in the whole of PFGs, a change in any one of the relative species abundance of PFGs would have primarily altered the comparison of the other PFGs in the plant community. Additionally, these contributions of PFGs on species richness appeared to be associated with climatic conditions (Li et al., ; Pan et al., ; Yan et al., ), and were highly identity‐dependent in grazed grasslands (Díaz et al., ; Lavorel et al., ; Noy‐Meir, ; Su et al., ). Another possible reason behind the negative correlation may be that plant species or PFGs have strong interactions (competition or facilitation) under grazing or drought conditions (Maestre et al., ; Milchunas et al., ), suggesting that interactions with PFGs could play a major role in maintaining plant species richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the effect of various attributes of biodiversity on ecosystem functioning, including evenness49, dominance50, and functional traits51 have been studied, the relative importance of compensatory mechanisms in natural ecosystems and the concept of compensation as a whole has largely been ignored despite evidence for the occurrence of compensation in natural systems52. Importantly, our simulations reveal that the mixing depth of sediment-dwelling invertebrate communities will depend on how compensatory behaviour is expressed, and the extent to which the functional attributes of compensating species affect bioturbation.…”
Section: Discussionmentioning
confidence: 99%
“…When the contributions of species to ecosystem function are driven by dominance rather than because of their unique effect traits, biomass compensation should mitigate the impact of changing species composition on ecosystem function (Davies et al 2011, Pan et al 2016). Changes in species composition can alter ecosystem function even if compensatory dynamics cause total biomass to remain stable, because of functional trait differences between species.…”
Section: Introductionmentioning
confidence: 99%